Skor CHADS2, CHA2DS2-VASc dan Atherosklerosis pada pasien Stroke Iskemik di RS dr. Zainoel Abidin Banda Aceh - Imran Isa; Farida; Devi Yanti (Journal of Medical Science, 2024)
ABSTRACT Atherosclerosis results from the accumulation of lipid complexes in the tunica intima of blood vessels and is associated with several risk factors for stroke. The CHADS2 and CHA2DS2-VASc scores were associated with stroke risk factors such as hypertension, DM, stroke-history/TIA, and advanced age. This study aims to determine the relationship between CHADS2 and CHA2DS2-VASc scores with atherosclerosis in ischemic stroke patients. This research is observational with cross sectional approach. The study sample was ischemic stroke patients who were treated in the nervous room of Dr. Zainoel Abidin Hospital Banda Aceh June-September 2022. Atherosclerosis was assessed using a Transcranial Doppler (TCD) device by measuring the pulsatile index of the left and right middle cerebral arteries (ASM). The study sample was 60 ischemic stroke patients, consisting of 35 men (58.3%) and 25 women (41.7%). Stroke infarct patients with atherosclerosis showed a relatively similar mean pulsatile index of the left (1.15 + 0.17) and right (1.15 + 0.18) middle cerebral arteries. The increase in CHADS2C and CHD2DS2C-VASc scores was followed by an increase in the pulsatile index of the left and right middle cerebral arteries. Stroke infarct patients who have atherosclerosis are 76.7%. CHADS2C and CHD2DS2C-VASc scores showed a significant relationship with atherosclerosis in ischemic stroke patients (CI95%, p=0.000). Keyword: CHADS2C score, CHD2DS2C-VASc score, atherosclerosis and ischemic stroke. ABSTRAK Atherosclerosis terjadi akibat penimbunan kompleks lipid di dalam tunika intima pembuluh darah dan berhubungan dengan beberapa faktor risiko stroke. Skor CHADS2 dan CHA2DS2-VASc terkait dengan faktor risiko stroke seperti hipertensi, DM, riwayat-stroke/TIA, dan usia lanjut. Penelitian ini bertujuan untuk mengetahui hubungan skor CHADS2 dan CHA2DS2-VASc dengan atherosclerosis pada pasien stroke iskemik. Penelitian ini bersifat observasional dengan pendekatan cross sectional. Sampel penelitian adalah pasien stroke iskemik yang dirawat di ruang saraf Rumah Sakit dr Zainoel Abidin Banda Aceh Juni-September 2022. Atherosklerosis dinilai menggunakan alat Trancranial Doppler (TCD) dengan mengukur pulsatile index arteri serebri media (ASM) kiri dan kanan. Sampel penelitian adalah 60 pasien stroke iskemik, terdiri atas 35 pria (58.3%) dan 25 wanita (41.7%). Pasien-pasien stroke infark yang mengalami atherosklerosis menunjukkan pulsatile index rata-rata arteri serebri media kiri (1.15 + 0.17) dan kanan (1.15 + 0.18) yang relatif sama. Peningkatan Skor CHADS2C dan CHD2DS2C-VASc diikuti peningkatan pulsatile index arteri serebri media kiri dan kanan. Pasien stroke infark yang mengalami atherosclerosis adalah sebesar 76.7%. Skor CHADS2C dan CHD2DS2C-VASc menunjukkan hubungan bermakna dengan atherosklerosis pada pasien stroke iskemik (IK 95%,p=0.000). Kata kunci: Skor CHADS2C, skor CHD2DS2C-VASc, aterosklerosis dan stroke iskemik.